Method Development for the Simultaneous Estimation of Prazosin and Polythiazide by UPLC Using QbD Approach - Bhavani, Pydi Geetha; Devi, Durairaj Akila (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction Prazosin is a quinazoline derivative and a selective antagonist of the α1 adrenergic receptor. The atomic structure is C19H21N5O4 and its molecular weight is 383.41 Prazosin is a helpful medication for managing and treating various illnesses. Through the thiazide-sensitive Na-Cl co-transporter, at the early distal tubule the diuretic polythiazide prevents active chloride re-absorption, increasing the excretion of water, salt and chloride. Its molecular formula is C11H13ClF3N3O4S3. Materials and Methods The chromatographic settings were optimized using Design Expert Software. Column used is DIKMA spursil Column C18 (2.1x50 mm; 3.0 micrometre), ratio of the mobile phase KH2PO4: Methanol (45:55), pH 3 phosphate buffer. Results The flow rate 0.3 mL/min. Run time: 5 min, wavelength: 265 nm, injection volume: 4 μL. For polythiazide and prazosin, the % RSD of precision was found to be 0.8 and 0.2, respectively. Polythiazide and Prazosin had accuracy of 100.15 and 100.30, linearity COR is 0.999 for both drugs, the corresponding LOD and LOQ were determined to be 2.91 and 10.04, accordingly. The percentages of Studies on acid, base, peroxide, thermal and photodegradation revealed that 0.27, 3.93, 10.66, 7.36 and 7.07. Conclusion The UPLC-QbD validated method is used to determine the amounts of Polythiazide and Prazosin. This approach assessed the system's suitability, specificity, sensitivity, accuracy, linearity, precision and robustness according to ICH standards.
Keywords: Polythiazide; Prazosin; International Conference Harmonization; UPLC; Quality by Design